Two-dimensional Numerical Simulations of Mixing under Ice Keels Videos - De Abreu, Sam; Cormier, Rosalie M.; Schee, Mikhail G.; Zemskova, Varvara E.; Rosenblum, Erica; Grisouard, Nicolas (Zenodo, 2023)
This deposition contains videos of all 16 two-dimensional mixing simulations of two-layered flow under the cross-section of an ice keel (see https://doi.org/10.5281/zenodo.8170312 for the simulation code). The videos use a BWR color scale to depict the vorticity field with black density contours overlaid. The simulations are organized according to two dimensionless quantities that specify the setup: The bulk Froude number (F) and the dimensionless keel draft (H). The files are then named accordingly. For example, F15H20 is F=1.5 and H=2.0, F10H12 is F=1.0 and H=1.2, etc.